AB0616 RO/SSA Autoantibodies in A Cohort of 552 Scleroderma Patients. (10th June 2014) - Zanatta, E.; Favaro, M.; Pigatto, E.; Bourji, K.; Polito, P.; Miatton, P.; Rizzo, M.; Tonello, M.; Cozzi, F.
Abstract : Background: Autoantibodies to Ro/SSA antigens have been demonstrated in 15-38% of patients with Systemic sclerosis (SSc) but their association with clinical manifestation and other serological patterns is not clear (1, 2, 3). Objectives: The aim of our study was to verify the prevalence of anti-SSA pattern in our cohort of patients with SSc. We also analyzed the clinical features of these patients, particularly the organ involvement. Methods: The retrospective review involved patients with SSc admitted to the Rheumatology Unit (University of Padova) from 1983 to 2013. By our data-base we obtained the demographic characteristics of patients, the antinuclear antibodies (ANA) specificity and the prevalence of the main visceral involvement. ANA were assayed by counter-immunoelectrophoresis (CIE). Lung involvement (ILD) was diagnosed if DLCO was <70% of predicted and forced vital capacity was <75% of predicted, or interstitial disease was note on chest radiogram or on HRTC. Heart involvment was defined in the presence of conduction defects or arhytmias on ECG and/or left ventricular diastolic dysfunction on echocardiogram. Pulmonary arterial hypertension (PAH) was estimated by Doppler echocardiogram (>45 mm Hg). Scleroderma renal crisis was defined by rapidly progressive renal failure and malignant arterial hypertension. Results: Our cohort consisted of 552 SSc patients, 71 males (13%) and 481 (87%) females, with mean age at diagnosis of 46.9±14.1 yrs; 155 patients (28%) were affected by diffuse and 397 (72%) by limited cutaneous form of SSc. ANA were positive in all patients. Anti-SSA pattern was found in 23 cases (4.2%); it was associated to anti-topoisomerase I in 15 (65.2%) and to anti-centromere in 8 (34.8%). Patients with anti-SSA pattern were 19 women and 4 men, with mean age at diagnosis of 49.6±12.9 yrs; 14 had the diffuse (60.9%) and 9 the limited cutaneous form (39.1%) of SSc. ILD was diagnosed in 14 cases (60.9%), cardiomyopathy in 4 (17.4%), PAH in 2 (8.7%). No patient developed scleroderma renal crisis. The frequency of organ involvement was similar to that of the entire cohort of SSc patients, except for scleroderma renal crisis. Conclusions: The prevalence of anti-SSA pattern in our cohort of SSc patients was lower than that reported by other Authors, probably because the assay method (CIE) was more specific but less sensitive than others. Anti-SSA autoantibody does not seem to affect the clinical features, in particular the visceral involvement. This conclusion is in agreement with Parker et al. (1) and Fujimoto et al. (2), while Hudson et al. report a higher frequency of ILD in patients with anti-SSA pattern (3). References: Parker JC, Burlingame RW, Bunn CC. J Autoimmune Dis. 2009; 6;6:2. Fujimoto M, Shimozuma M, Yazawa N et al. Ann Rheum Dis. 1997; 56:667-70. Hudson M, Pope J, Mahler M et al. Arthritis Res Ther. 2012, 14:R50. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5134